XRD Analysis Procedure For Clay Minerals – Application To Chachimbiro Geothermal System - Guillén Pachacama, Doménicca Mileth (2020)
This study comprises concepts about geothermal systems, their classification, exploration and exploitation with emphasis in Ecuador advance. Also, it involves principles about hydrothermal alteration and clays as descriptive clue. Besides, with the purpose to contribute to national knowledge, this research composes a laboratory procedure for clay mineral preparation to XRD analysis. It was structured by contrasting stablished methodologies but also based on conclusions empirically obtained during the experimentation in the Instituto de Investigación Geológico y Energético. The applicability of this newly procedure was remarked with the identification of five different clays in PEC1 geothermal well of Chachimbiro. Assuming they were on a stablish regime, we present two considerable advances. First, there is an illitization processes which guarantees a high increase of temperature with depth and implies the existence of argillic alteration. It allows us to suggest that the clay cap of Chachimbiro geothermal field is thicker than 340 m as other authors hold. Second, according to the temperature profile we propose a maximum temperature of 170°C until 310 meters depth and 240°C to 260°C, at greater depths than 700 meters.